Prevalencia del Stephanurus dentatus adultos ninfas y huevos en cerdos faenados en el matadero municipal de Bahía de Caráquez, cantón Sucre - Farías Chica, Mariuxi Antonella (2021)
The objective of this research was to determine the prevalence of the adult worm, nymphs and eggs in the urine of Stephanurus dentatus in pigs slaughtered in the municipal slaughterhouse in Bahía de Caráquez, Sucre canton, by observing the adult parasite in the kidney and eggs in laboratory samples. Analysis of absolute frequencies, expected frequencies under independence and the Chi square value with a significance level of 0.05% were used using the statistical package InfoStat version 2020; the results show that there is no dependence on the presence of the adult stage of the parasite in the urine due to age and the rearing system, nor was it found that the presence of nymph in the urine depends on age, production systems and sex of pigs. However, a significant difference was found that shows that the presence of the parasite in the adult state in the urine of pigs is dependent on sex and age (p = 0.01). The results show that there is a prevalence of the parasite Stephanurus dentatus in the adult, nymph and egg stages in the urine of pigs slaughtered in the Bahía de Caráquez municipal slaughterhouse, Sucre canton.